Phytoplankton species diversity and abundance in satellite lakes of Lake Victoria basin (Tanzanian side) - Sekadende, BC; Mbonde, ASE; Shayo, S; Lyimo, TJ (Tanzania Journal of Science, 2021)
Studies on phytoplankton species diversity and abundance were carried out in 8 selected satellite lakes within the Lake Victoria basin during two wet seasons (March-April 2002 and January-February 2003) and one dry season (August-September 2002). Higher species richness (76 species) of phytoplankton species was recorded in rain season than in dry season (47 species). The observed species represents six classes, cyanophytes, chlorophytes, cryptophytes, basillariophytes, euglenophytes and dinophytes, of fresh water algal flora. Species diversity was generally low, with diversity indices (H\') ranging from 0.21 for Lake Kyarano to 0.09 for Lake Ikimba. On the contrary, Lake Katwe was richer in terms of species (66) followed by Burigi (49) and Ikimba (47). Lake Kubigena represented a lowest number (17) of species. Lake Burigi showed the highest abundance (611624 cell/ml) in rain season, while Lake Kyarano showed the lowest abundance (1336 cells/ml) recorded in dry season. Cyanophytes dominated (75-98% of counted cells) the phytoplankton community throughout the study period followed by bacillariophytes (0.2 -14% of counted cells) in all lakes except Lake Kyarano, which was dominated by Dinophytes (71%), whereas euglenophyta and chrysophyta were rarely encountered. The results clearly show that the phytoplankton community of satellite lakes were largely dominated by cyanophytes. This may indicate high nutrient loading (pollution) in these lakes that are certainly resulting from the surroundings. These findings call for a special attention on cyanobacteria occurrence and their unforeseen effects such as toxin production and oxygen depletion during nights that may results into fish killings.